Barthes's Imaginary Voyages - Lynn A. Higgins (Studies in 20th & 21st Century Literature, 1981)
Reading L 'Empire des signes and Alors la Chine as points of departure, the article explores a network of reciprocal images of the text as voyage and the voyage as text, with Barthes as a self-styled, disinherited ethnographer/traveler.
Keywords: L ' Empire des signes; Alors la Chine; voyage; text